A hybrid active filter for damping of harmonic resonance in industrial power system - Felani Stefanzie Choe @ Felani Syahnizam, 1986-; Alias Mohd. Yusof; Fakulti Kejuruteraan Elektrik (2009)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2009